The Relationship between Nomophobia and Perceived Socialization in the Online Learning Environment - Karabatak, Songul; Ay, Sevinc; Karabatak, Murat (Ieee, 2022)
This research aimed to examine the relationship between teacher candidates' nomophobia behavior tendency and their perceptions of socialization in the online environment. For this purpose, the research was designed in the relational survey model within the scope of quantitative research. The sample of the research consists of teacher candidates at the Faculty of Education at Firat University. To collect the data, the Nomophobia Questionnaire and the Perceived sociability in the online learning environments Scale were used. At the end of the study, it was revealed that the nomophobia behavior tendencies of the teacher candidates were at a moderate level and their perceived socialization in the online learning environment was at the level of undecided. The nomophobia levels of female teacher candidates were found to be significantly higher than males, but the perceived socialization levels of teacher candidates in the online learning environment do not differ significantly according to the gender variable. According to another finding of the study, the teacher candidates' nomophobia levels changed according to the grade variable. The teacher candidates' nomophobia levels differed significantly between the 1st and 2nd grades in general. It was also seen that there was a positive, significant, and low-level relationship between the nomophobia levels of teacher candidates and their perceptions of socialization in the online learning environment. Various suggestions are presented regarding the results obtained from the study.
10th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 06-07, 2022 -- Maltepe, TURKEY
Keywords: nomophobia; perceptions of socialization; online environments